Protein Kinase Cη : regulation of expression and functional role in human T lymphocytes - Nierop, Denise Triglia van (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2014)
Protein kinase Cη (PKCη) is a member of the novel PKC subfamily of serine/threonine kinases that has been shown to play critical roles in cell differentiation, proliferation, secretion and apoptosis in several cell types. This isoform is primarily expressed in epithelial tissues but it has also been shown to be expressed at high levels in T cells. T cells are the centre of cell-mediated immunity, responsible for recognising, with high specificity through their T cell receptor (TCR), antigenic peptides presented by specialised cells and responding by orchestrating an effective immune response. Stimulation of the TCR and co-receptors triggers a complex signalling cascade that results in T cell activation, cytokine production, proliferation and differentiation into effector cells.
Keywords: Clinical Medicine, Ph.D.; Ph.D. Trinity College Dublin